Revolutionizing supply chains: Unveiling the power of blockchain technology for enhanced transparency and performance - Lee, Khai Loon; Zhang, Tianyang (GAFTIM, 2023)
In recent years, the significance and prevalence of distributed ledger technology have grown. However, there is a lack of empirical studies examining the managerial and technological aspects essential for implementing it in the distribution network. The objective of this research is to develop a comprehensive framework for the adoption of blockchain technology in the entire distribution chain. This will be achieved by identifying the factors that facilitate adoption and experimentally evaluating their interdependencies and effects on adoption through empirical evidence collection. A quantitative approach was used to assess the model's main objective. The study focused on the medicine manufacturing industry to gather responses regarding the intention to use blockchain technology and its impact on supply chain performance. The findings revealed a significant positive relationship in the hypothetical model. Additionally, secondary data analysis, which considered previous research and online surveys, was conducted to assess the impact of blockchain technology on supply chain performance and the mediating role of supply chain transparency.